Banca non lending - Bayona Mac Pherson, Tiksi (2023)
Within the Peruvian financial system, the current Commercial Banking2 market is very competitive. Different entities seek to capture the largest number of business clients (large, medium, mid-market and businesses) to be able to provide facilities through financing, cash management operations, leasing, exchange rate operations and other appropriate financial transactions. to the market and the needs. The main business of commercial banking is to provide loans, the return would be based on the returns generated by working capital and transaction flow. A segment of commercial banking clients that, to date, has not been served by the financial system, are those companies with surpluses, those that have liquidity in their accounts. This is due to the fact that they have their own resources or because they operate with the resources of their parent company. This means that loans, financing or some form of external leverage are not essential, a situation that leads to this type of client not being the focus of attention of bank officials. However, it opens up a possibility to generate a new business model for corporate -through non-financial operations such as the exchange rate, collection, correspondent services, bill collection, supplier payment, payroll payment, tax payment, among other transactions where the risk is nil and operating costs are very low. The implementation of this system would generate profitability for corporate banking where it is applied with an internal rate of return of up to 44 %.